Improved detection of hepatocellular carcinoma by dynamic computed tomography in cirrhotic patients with chronic hepatitis B: A multicenter study. Issue 10 (20th April 2020) - Kim, Ji Hyun; Kang, Seong Hee; Lee, Minjong; Choi, Hoon Sung; Jun, Baek Gyu; Kim, Tae Suk; Choi, Dae Hee; Suk, Ki Tae; Kim, Moon Young; Kim, Young Don; Cheon, Gab Jin; Baik, Soon Koo; et al.
Abstract: Background and Aims: Current guidelines for chronic hepatitis B (CHB) patients are to undergo surveillance for hepatocellular carcinoma (HCC) with 6‐monthly ultrasonography (US). However, sensitivities of US to detect early‐stage HCC in cirrhotic patients are suboptimal. We aimed to compare overall survival and detection rates of very‐early‐stage HCC in two groups: group A, undergoing 6‐monthly US versus group B, undergoing 6‐monthly US alternating with dynamic computed tomography (CT). Methods: This retrospective multicenter study assessed 1235 cirrhotic patients with CHB under entecavir/tenofovir therapy from 2007 to 2016. The primary endpoint was overall survival rates between the two groups. The Cox proportional hazards model and propensity score matching analyses were used to assess the effect of surveillance modalities on overall survival and detection of Barcelona Clinic Liver Cancer stage 0 HCC after balancing. Results: During a median follow‐up of 4.5 years, 10‐year cumulative HCC incidence rates of 16.3% were significantly higher in group B ( n = 576) than 13.7% in group A ( n = 659; P < 0.001). However, in patients with HCC, 10‐year overall survival rates of 85.1% were significantly higher in group B than 65.6% in group A ( P = 0.001 by log‐rank test). CT exam alternating with US was independently associated with reduced overall mortality (hazard ratio 0.47, P = 0.02). Cumulative incidence of Barcelona Clinic Liver Cancer stage 0 HCC was significantly higher in group B than in group A (hazard ratio 2.82, P < 0.001). Conclusion: In cirrhotic patients with CHB, dynamic CT exam alternating with US led to higher detection rates of very‐early‐stage HCC and benefit of overall survival than did US exams.